STUDY ON THE IMPLEMENTATION OF THE BALANCE FUND POLICY AND ITS IMPLICATIONS ON THE MINIMUM SERVICE STANDARDS FOR SUSTAINABLE DEVELOPMENT IN THE CITY OF PEKANBARU - Fendri Jaswir; Sufian Hamim; Rahyunir Rauf (RADJA PUBLIKA, 2025)
The purpose of this study is to Analyzing and Explaining the Implementation of the Balanced Fund Policy Its Implications on the Minimum Service Standards for Sustainable Development in the City of Pekanbaru. This research uses the theory of the implementation of Edward III's policy and Government Regulation Number 2 of 2018 concerning Minimum Service Standards and Minister of Home Affairs Regulation Number 100 of 2018 concerning the Implementation of Minimum Service Standards, as guidelines in the preparation of planning documents in the implementation of SPM in the area of the head office. Therefore, the Development of Competence in the Preparation of Planning Documents in terms of the implementation of SPM in the Scope of the Head Office area will provide a clear overview of the vision, mission, goals and strategies as well as the direction of regional development policies as well as the minimum service standards that have been promised to the community.